Феноменология на службе языкознания. Принцип симультан-ности - Siankevich, Vasili (Acta Polono-Ruthenica, 2021)
In the humanitarian field, conventional institutions and existing institutes of knowledge give place to the paradoxical experience of knowing the obvious reality by means of art. This non-discursive experience does not have access to the sphere of linguistic forms and paradigms; however, it receives a logistic embodiment in the word that can be heard in real time. It is the task of phenomenological linguistics to learn the motives and reflexes of the invaluable experience of a person’s meeting with the true reality embodied in the living word. The article addresses the issue of the orthodox inconsistency of traditional linguistics in understanding linguistic essences. Phenomenology paves the way for an antinomical study of the language, supplementing the existing paradigms of analysis with its characteristic principles. In the light of the principle of simultaneity, the meaning of derivations characteristic of linguistic creativity becomes accessible, not excluding mythology.